Modelling of a paraboloid antenna for receiving and its equivalent circuit - Gao, Xiang; Du, Zhengwei (IET microwaves, antennas & propagation, 2014)
This study presents a SPICE model of a paraboloid antenna for receiving. The proposed model is converted from a receiving model based on the Thévenin's theorem and the reciprocity theory through rational approximation. The model gives the coupling voltages on the antenna load when the antenna is illuminated by plane waves. This model can be used in both frequency-domain and time-domain analyses, and can be a part of a system-level model for electromagnetic compatibility simulation in circuit solvers. The proposed model has been verified by several examples.